THEORETICAL FOUNDATION OF TECHNOLOGY IN MODERN EDUCATION - Mohigul Soliboyeva; Eshdavlatova Adiba Zafarovna (TADQIQOTLAR, 2026)
Abstract In the endeavor to construct a contemporary socialist nation, the synchronized advancement of education, science and technology, and human resources has emerged as a crucial element in enhancing national competitiveness. This research emphasizes educational technology as a pivotal connecting component that integrates these three domains, fostering a vibrant ecosystem for learning and talent cultivation. Educational technology not only facilitates effective teaching and individualized learning but also encourages collaboration between educational institutions and the industry, while aiding in the modernization of educational assessment frameworks.